2008
DOI: 10.1161/strokeaha.107.499236
|View full text |Cite
|
Sign up to set email alerts
|

Circulating Endothelial Progenitor Cells as a New Marker of Endothelial Dysfunction or Repair in Acute Stroke

Abstract: Background and Purpose-Understanding on distinct subsets of endothelial progenitor cells may provide insights of endothelial dysfunction or repair in the acute ischemic event. Recent in vitro data have reported the colony-forming unit (CFU) and outgrowth cell population as a subset of endothelial progenitor cells. In this study, we undertook to validate the significance of CFU number and outgrowth cell yield in acute stroke. Methods-Mononuclear cells were isolated from the peripheral blood of 75 patients with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
101
0
1

Year Published

2008
2008
2013
2013

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 108 publications
(107 citation statements)
references
References 34 publications
5
101
0
1
Order By: Relevance
“…The number of cells was measured, however, B1 week after the stroke, which might be too late to measure the 'true' reparative cells. 32 …”
Section: Strokementioning
confidence: 99%
“…The number of cells was measured, however, B1 week after the stroke, which might be too late to measure the 'true' reparative cells. 32 …”
Section: Strokementioning
confidence: 99%
“…Colonies were counted manually in a minimum of 3 wells in 12-well plates by two independent observers who were unaware of clinical profiles; results are expressed as average number of CFUs per well. In selected samples, the endothelial phenotype was confirmed using specific indicators, that is, according to the uptake of 1,1 0 -dioctadecyl-3,3,3 0 ,3 0 -tetramethylindocarbocyanine-labeled acetylated low-density lipoprotein (Biomedical Technologies Inc., Stoughton, MA, USA), and by immunostaining using FITC-labeled Ulex europaeus agglutinin-1 (Sigma) and anti-CD31 (1:20; DAKO, Carpinteria, CA, USA), antivascular endothelium cadherin (1:50; Chemicon, Billerica, MA, USA), anti-CD34 (1:20; DAKO), and anti-kinase domain receptor (1:50; Sigma) antibodies, as previously described (Hur et al, 2004;Yoon et al, 2005;Chu et al, 2008;Jung et al, 2008).…”
Section: Colony-forming Unit Countsmentioning
confidence: 99%
“…Furthermore, it was recently suggested that reduced numbers and impaired functions of circulating EPCs are related to the pathogenesis of stroke (Ghani et al, 2005;Chu et al, 2008). Thus, given that MMD involves dynamic interplay between arterial occlusion and neovascularization, the involvement of EPCs in MMD may be more complex than in other cerebrovascular occlusive diseases.…”
Section: Introductionmentioning
confidence: 99%
“…On the positive side, in animal studies, EPCs have been shown to participate in the formation of new vessels and to increase blood flow in ischemic areas. 25 Increased levels of circulating EPCs and reduced ischemic damage were found after diabetic mice with middle cerebral artery occlusion were infused with EPCs preincubated with wildtype membrane microparticles. 18 EPC numbers can be increased by exercise and with ACE inhibitors and receptor blockers, statins, and erythropoietin.…”
mentioning
confidence: 99%
“…These immature endothelial cell-derived bone marrow stem cells circulate in peripheral blood. 24,25 Endothelial injury appears to act as a trigger for these cells in the repair of damaged endothelial cells. Such a potential "miracle cure" has both benefits and risks.…”
mentioning
confidence: 99%